The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00429-021-02408-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of the anatomical fiducials framework to a clinical dataset of patients with Parkinson’s disease

Abstract: Establishing spatial correspondence between subject and template images is necessary in neuroimaging research and clinical applications such as brain mapping and stereotactic neurosurgery. Our anatomical fiducial (AFID) framework has recently been validated to serve as a quantitative measure of image registration based on salient anatomical features. In this study, we sought to apply the AFIDs protocol to the clinic, focusing on structural magnetic resonance images obtained from patients with Parkinson’s disea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A Wilcoxon signed-rank test revealed no significant differences between any LEs in all axes. Furthermore, we expanded our analysis to a subset of 24 patients who previously had AFIDs placed by five raters (Abbass et al, 2022; Lau et al, 2019; Taha et al, 2023). The median AFLE (IQR) ranged from 0.56 mm (0.40-0.69 mm) for AFID02 (PC) to 2.25 mm (1.49-2.75 mm) for AFID25 (right inferior anteromedial temporal horn).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A Wilcoxon signed-rank test revealed no significant differences between any LEs in all axes. Furthermore, we expanded our analysis to a subset of 24 patients who previously had AFIDs placed by five raters (Abbass et al, 2022; Lau et al, 2019; Taha et al, 2023). The median AFLE (IQR) ranged from 0.56 mm (0.40-0.69 mm) for AFID02 (PC) to 2.25 mm (1.49-2.75 mm) for AFID25 (right inferior anteromedial temporal horn).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported and openly released AFIDs annotations in a population of thirty-nine patients undergoing STN DBS for PD (Abbass et al, 2022; Taha et al, 2023). Briefly, 5 raters localized AFIDs on subject scans and on the MNI template.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, Abbass et al recently reported utilization of anatomical fiducials in the brain for such a purpose. However, this method includes the placement of 32 fiducial points which is impractical for clinical application [35]. Therefore, as automated segmentation tools continue to evolve, efficient and reliable methods of QC are needed to make them more clinically relevant.…”
Section: Quality Controlmentioning
confidence: 99%